Makna Hidup Kudus Menurut 1 Petrus 1:13-16 dan Aplikasinya Bagi Pemuda-Pemudi Kristen Masa Kini - Riawan Riawan; Abad Jaya Zega (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
There are actions of Christians who no longer live by maintaining holiness in their daily behavior, and the importance of living life as believers by maintaining holiness before God. This article aims to provide a correct understanding of the writings of the Apostle Peter regarding the importance of maintaining a life of holiness so that it can be significant in the lives of believers, especially for the next generation of the Church. This research uses qualitative methods, by analyzing various sources such as books, journals, articles related to the title to be discussed. The results of the analysis see that it is very important for believers to maintain holiness for God. Every believer, not only the simple people, is expected to live in holiness by avoiding all uncleanness for God. The contents of this article are intended to make readers aware of the importance of living a holy life. It is hoped that this research will be able to contribute to the ideas of every reader, especially Christians, so that they can maintain the holiness of their lives properly and fear God.